2021
DOI: 10.1038/s41598-021-03368-8
|View full text |Cite
|
Sign up to set email alerts
|

Returning to work after a sickness absence due to cancer: a cohort study of salaried workers in Catalonia (Spain)

Abstract: Cancer incidence and survival rates have increased in the last decades and as a result, the number of working age people diagnosed with cancer who return to work. In this study the probability of accumulating days of employment and employment participation trajectories (EPTs) in a sample of salaried workers in Catalonia (Spain) who had a sickness absence (SA) due to cancer were compared to salaried workers with SA due to other diagnoses or without SA. Each individual with SA due to cancer between 2012 and 2015… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…In Switzerland, elementary occupations have the highest proportion (>60%) of part-time workers, three-fourths of whom are women [ 63 ]. Depending on whether part-time work was voluntary or involuntary (when it was impossible to return to full-time work) [ 18 ], it could be either protective or a risk factor for survival. However, the evidence is very scarce.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Switzerland, elementary occupations have the highest proportion (>60%) of part-time workers, three-fourths of whom are women [ 63 ]. Depending on whether part-time work was voluntary or involuntary (when it was impossible to return to full-time work) [ 18 ], it could be either protective or a risk factor for survival. However, the evidence is very scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we could not fully rule out a selection bias. Assigning occupations as a time-dependent variable based on two time points could result in some misclassification, especially given that cancer survivors have a less stable employment trajectory than other workers [ 18 ]. Nevertheless, the information on the occupation at the time of the federal censuses is correct and we believe we assigned it accurately enough, since the majority of patients kept the same occupation between the two censuses [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Characterising the working paths of cancer survivors may shed light on how surviving the disease and subsequent career decisions may interact in the long term. In a previous study, we showed that cancer survivors are less likely to accumulate days of employment in the long term [12]. On the one hand, these changes in survivors' working life may be driven by personal decisions due to health or financial status or a desire to modify career paths after a reassessment of life priorities [13].…”
Section: Introductionmentioning
confidence: 91%